Cost optimal nZEBs in future climate scenarios. (September 2017) - Ferrara, Maria; Fabrizio, Enrico
Abstract: The key-concepts of nearly Zero Energy Building (nZEB) and cost optimality have driven many research activities across Europe in recent years. Considering the ongoing global changes, it is necessary to study and guarantee the resilience of the nZEB design to the variations of the boundary conditions in which the cost optimal calculation is performed. We present the analysis of the variation of the cost-optimal design of a single-family house in a continental climate (Paris) in different climate change scenarios in the short-medium term (2026-2045). The main finding from the results analysis is that the higher the energy performance, the higher is the resilience to the variation of weather conditions.